Occurrence of efavirenz, levonorgestrel, ibuprofen, and diclofenac in wastewaters of limpopo province, South Africa - E.P. Munzhelele; W.B. Ayinde; W.M. Gitari; G.K. Pindihama; R. Mudzielwana (Heliyon)
This study aims to investigate the occurrence of efavirenz, levonorgestrel, ibuprofen, and diclofenac in wastewaters of Vhembe and Mopane District Municipalities, Limpopo Province, South Africa. A total of 48 samples were collected at the inlet and outlet of the selected wastewater treatment plants during April, July, and October 2023. The physicochemical parameters such as pH, electrical conductivity, total dissolved solids, and dissolved oxygen of the influent and effluent were determined in the field, while total organic carbon (TOC) and chemical oxygen demand (COD) were determined in the laboratory. The LC-20 prominence High-pressure liquid chromatography with a Photo-diode Array (PDA) detector was employed to quantify and profile the targeted pharmaceutical compounds. Levonorgestrel and efavirenz were analyzed using the gradient elution method, while the isocratic method was applied to analyze diclofenac and ibuprofen. The obtained results showed that the concentration ranges for ibuprofen were <LOD-114.00 μg/L (influent) and <LOD-59.9 μg/L (effluent), levonorgestrel: 6.2–8.09 μg/L (influent) and 4.25–20.9 μg/L (effluent), diclofenac: 2.21–25.00 μg/L (influent) and 0.36–5 μg/L (effluent), and efavirenz: 3.81–11.9 μg/L (influent) and 0.69–6.3 μg/L (effluent). The presence of these pharmaceutical contaminants in wastewater, particularly in effluent, requires attention as they may pose significant ecological threats in the receiving water bodies. Therefore, this study recommends the development of efficient wastewater treatment technologies targeting pharmaceutical compounds and further routine monitoring of these compounds in surface water resources, as well as understanding their fate and effects in aquatic organisms.